UTILIDADE DO TESTE DO GLUCAGON NO DIAGNÓSTICO DAS DEFICIÊNCIAS DE GH E CORTISOL EM PEQUENAS LESÕES HIPOFISÁRIAS. - ROCHA, Viviane Chaves de Carvalho (2018)
The consensus in the literature is that the hypothalamic–pituitary axis should be investigated with stimulus tests only for pituitary lesions larger than 1 cm. Pituitary tumors smaller than 1 cm may present deficiencies of growth hormone and cortisol to the stimulus tests. We evaluated the response of growth hormone and cortisol to the glucagon test of 3 h duration (fixed dose: 1mg and 1,5mg Glucagon on 90 kg and ≥ 90kg, respectively) in 40 patients with pituitary lesions smaller than 1 cm, followed by an insulin tolerance test (ITT) to confirm the deficiencies. In the glucagon test, 3.7% (n=1) of the microprolactinomas did not respond to growth hormone (<3 ng/mL) and 77.8% (n= 21) presented cortisol values >18 μg/dL, while 37.5% of the nonfunctioning microadenomas had a sub-growth hormone (GH deficiency). All 40 patients had growth hormone value >1 ng/mL. Deficiencies of growth hormone and cortisol were not confirmed by the ITT in patients who had on Glucagon Test deficiencies . Our findings demonstrate that the glucagon test has a high number of false positive results with higher cutoff values. The glucagon test has been shown to be a safe option when there is a contraindication to the ITT. Stimulus tests should not be routinely indicated for evaluation of the hypothalamic–pituitary axis in cases of lesions smaller than 1 cm, except in cases where there are metabolic or clinical alterations suggestive of such deficiencies or progressive decreases of insulin-like growth factor 1 (IGF-1) and cortisol during routine follow-up of these patients. There is a need for adequate cutoffs for both growth hormone and cortisol.